PERSEPSI MASYARAKAT TENTANG DAMPAK PEMBANGUNAN BANDARA INTERNASIONAL MINANGKABAU (BIM) TERHADAP STATUS SOSIAL EKONOMI DI KENAGARIAN KATAPING - PUJI LESTARI; afdhal afdhal (JURUSAN GEOGRAFI FIS UNP, 2019)
The purpose of this research is to find out how the public perception about the impact of the construction of the Minangkabau International Airport (BIM) on socio-economic status in Kenagarian Kataping.This type of research is descripive quantitative research. The Population and sample in this study were people in Kenagarian Kataping, Batang Anai sub-district, Padang Pariaman Regency. data is done through observation and questionnaires. The research data is analyzed using a Percentage and Likert formula.The results of the study show. (1). The community economy is in the high category with a percentage of 21,6 %, the medium category with a percentage of 66,0%, and a low category with a percentage of 12,4%. thus the community economy is in the medium category. (2). Social Society, is in the high category with a percentage of 18,6%, medium category with a percentage of 70,1%, and a low category. (3). Community infrastructure is in the high category with a percentage of 19,6%, medium category with a percentage 0f 69,1%, and a low category with a percentage of 11,3%. Thus community infrastructure is in the medium category.